Axial strain accumulation projection model for sand in cyclic loading. Issue 147 (August 2021) - Xia, Pingxin; Zeng, Chao; Shao, Longtan; Zhang, Xiong
Abstract: Strain accumulation analysis is important to understand the deformation mechanism of soil structure subjected to cyclic loading. An empirical model is a superior choice for the description of strain accumulation. However, the ambiguity and sensitivity for the physical meaning of the parameters in the empirical model hindered the understanding of the strain accumulation mechanism. Compared with conventional empirical models by directly fitting experimental data, this study proposed a new approach to formulate an empirical model of strain accumulation using the intrinsic relationship between the reloading process in cyclic loading and the monotonic loading process. All axial strain accumulation increments of silica powder during cyclic loading with constant cyclic stress amplitude were projected onto the corresponding monotonic loading stress-strain curve, and the evolution of strain accumulation was described by the projection modulus, which was regarded as an intrinsic parameter of the projection stress-strain curve. An empirical formulation for describing the connection between projection modulus and stress levels was proposed. In addition, the prediction model of total axial strain in cyclic loading was presented by combining the accurate representation of elastic and plastic moduli during primary loading. Finally, discussions on the intrinsic relation mentioned above were enhanced by presenting more experimental evidence. This paper provided novel insight into the mechanism of strain accumulation in cyclic triaxial conditions by linking strain accumulation with a unified stress-strain relation. However, limited by the triaxial stress conditions in this study, it is recommended to extend this projection method to other cyclic load tests. Highlights: Proposed intrinsic relation between the unloading-reloading process in cyclic loading and the monotonic loading process. Strain accumulation were projected onto the monotonic stress-strain curve. Projection stress-strain behaviors were studied by introducing projection modulus. Total axial strain during cyclic loading was described using three moduli: elastic modulus, plastic modulus, and projection modulus.